Implementation of International Safety Management (ISM) Code on Ro-Ro Ship of PT. Kalla Lines in Makassar - Bustamin Bustamin; Ismail Ismail; Darwis Darwis; Andi Dirga Noegraha (Cita Konsultindo Research Center, 2024)
The purpose of this study is to determine how much the level of implementation of the International Safety Management (ISM) Code in the shipping company PT Kalla Lines and on Ro-Ro ships operated in the shipping company. Based on data from the National Transportation Safety Committee (KNKT), 221 shipping accidents were investigated during 2007-2023, the majority of accidents were classified as ships on fire (33 percent) with one of the biggest focuses on roll-on/roll-of or ro-ro passenger ships, so it is necessary to determine the level of implementation of the ISM-Code in the shipping company PT Kalla Lines and its fleet of Ro-Ro ships. The type of research is descriptive qualitative, which can provide a clearer image of the implementation of the ISM Code. From the results of the analysis obtained the level of implementation the ISM-Code on ships operated by PT. Kalla Lines obtained an average (mean) according to scale of 2.59 or 86.24% is at the level of fulfilment, and the office of PT. Kalla Lines is 2.84 or 94.54% or meet the requirements of the ISM-Code.